Mechanical Strain Promotes Osteogenesis of BMSCs from Ovariectomized Rats via the ERK1/2 but not p38 or JNK-MAPK Signaling Pathways. - Zhang, P.; Dai, Q.; Ouyang, N.; Yang, X.; Wang, J.; Zhou, S.; He, N.; Fang, B.; Jiang, L. (Current Molecular Medicine, 2015)
Osteoporosis has become a world-wide health problem. As a promising intervention, mechanical strain is considered to be an important factor in bone remodeling. However, the underlying mechanisms are still not clarified clearly. In the present study, we aim to investigate the possible mechanism by which mechanical stimulation induces osteogenic differentiation of bone mesenchymal stem cells (BMSCs) from ovariectomized rats (OVX BMSCs). The results demonstrated that intermittent mechanical strain (IMS) promoted osteogenic differentiation of OVX BMSCs by activating Runt-related transcription factor 2 (Runx2). When the extracellular regulated kinase1/2-mitogen activated protein kinases (ERK1/2-MAPK) signaling pathway was blocked, the osteogenenic effects of IMS were diminished; while blocking of the p38-MAPK signaling pathway had little effect on subsequent osteogenic events. In addition, the phosphorylation level of JNK was not affected by IMS. Our results indicated that strain-induced osteogenic differentiation of OVX BMSCs may take effect via ERK1/2-MAPK not p38 or c-Jun N-terminal (JNK)-MAPK signaling pathway. These findings may have implications for physical treatment of osteoporosis in vitro.
Keywords: Runx2